Students’ Perception on the Use of Social Media to Promote Their Listening Skill - Dita Aprilia Dwi Pratiwi (Retain: Journal of Research in English Language Teaching, 2024)
Listening abilities have emerged as one of the most important language skills to master, particularly in English. Currently, social networking can help humans improve their English language skills. Many social media platforms can be used to improve English skills, including TikTok, Instagram, YouTube, Twitter, and others. This research aims to find out general information the students have on the use of social media and to know the students' perceptions of using social media to promote their listening skills. The research used a descriptive quantitative research method with a survey design. The sample used was the eleventh grade at one of the senior high schools in Surabaya in the academic years 2023/2024. The data instruments included a questionnaire and an interview, which were analyzed using the SPSS 27 program. According to the findings, students utilized social media for both personal and educational goals at various times and they used various types of social media for different purposes. The students have a positive attitude toward using social media to promote their listening skills. It can be seen from the interpretation of each question in the questionnaire which is supported by interview data.